A Macromolecular Drug for Cancer Therapy via Extracellular Calcification. Issue 12 (17th February 2021) - Tang, Ning; Li, Hanhui; Zhang, Lihong; Zhang, Xueyun; Chen, Yanni; Shou, Hao; Feng, Shuaishuai; Chen, Xinhua; Luo, Yan; Tang, Ruikang; Wang, Ben
Abstract: Cancer chemotherapy typically relies on drug endocytosis and inhibits tumor cell proliferation via intracellular pathways; however, severe side effects may arise. In this study, we performed a first attempt to develop macromolecular‐induced extracellular chemotherapy involving biomineralization by absorbing calcium from the blood through a new type of drug, polysialic acid conjugated with folate (folate‐polySia), which selectively induces biogenic mineral formation on tumor cells and results in the pathological calcification of tumors. The macromolecule‐initiated extracellular calcification causes cancer cell death mainly by intervening with the glycolysis process in cancer cells. Systemic administration of folate‐polySia inhibited cervical and breast tumor growth and dramatically improved survival rates in mice. This study provides an extracellular therapeutic approach for malignant tumor diseases via calcification that is ready for clinical trials and offers new insights into macromolecular anticancer drug discovery. Abstract : We propose a macromolecular‐drug‐induced extracellular chemotherapy involving biomineralization by absorbing calcium from blood. Polysialic acid combined with folate, which spontaneously induces biogenic mineral formation on cancer cells rich in folate receptors, leads to targeted pathological calcification and cell death. Systemic administration of folate‐polySia improves survival rates of tumor‐bearing mice with negligible side effects.